Performance diagnostics in elite biathlon: key factors and predictors - Sattlecker, G.; Dirnberger, J.; Wiesinger, H.-P.; Birklbauer, J.; Buchecker, M. (9th International Congress on Science and Skiing, March 18 - 22, 2023, Saalbach-Hinterglemm, Austria, 2023)
INTRODUCTION: Biathlon is a complex sport combining cross-country skiing and rifle shooting. The competition results are determined by the skiing time, shooting time, and shooting accuracy. The shooting performance in turn depends on postural balance, rifle stability, triggering behavior, and forces on the shoulder and sling in standing and prone positions (Laaksonen et al., 2018; Sattlecker et al., 2017). Our research on these variables, conducted for over 20 years in both shooting positions, provides athletes with a personalized strengths-weaknesses profile and recommendations to improve their shooting performance.